A Review of Forest Fire Science: Prevention and Detection (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2026)
Forest fires have profound effects on both ecosystems and communities, causing immediate destruction and long-term challenges. The impacts on ecosystems include habitat loss, soil degradation, air and water pollution and climate change speedup. The impact on communities include health risks, economic loss, displacement of communities and psychological effects resulting from trauma of losing homes and loved ones. The fight against forest fires involves prevention, early detection and suppression. In this article selected knowledge on forest fires (also known as wildfires) and the strategies and facilities that are available to fight against forest fires are reviewed. The worst scenarios will be highlighted by looking at some of the biggest fires that have happened across the world and the damage they have caused. It is crucial to understand the chemistry of fires (composition and chemical reaction), the causes of fires (natural and human-related), types of fires and the products of fires. These are important for wild fires management using the evolving green technologies. The review will then focus on prevention, early detection and aggressive suppression with a particular focus on the African and Tanzanian scenario. The paper will end by a design of an early detection system to protect a selected conservation area.